Tlingit village, Kasaan, Alaska, 1908 - Case, W. H., 1868-1920; Case, W. H. (William Howard), 1868-1920 Draper, H. H.
Tlingit village, Kasaan, Alaska, 1908, seen from a distance. In foreground is beach, with small boat; in background is the village, set in a clearing in front of trees. Copy print by Frank H. Nowell of a photograph by W. H. Case Caption on image: Native village Kasaan, Alaska, 1908